Strategi Peningkatan Kinerja UMKM Berbasis Praktik Keberlanjutan: Tinjauan Sistematis Literatur tentang Peran Ko-Inovasi dan Orientasi Kewirausahaan - Nur Aini Syarifah; Sri Utami Nurhasanah; Sarah Fitriyani (STIE KASIH BANGSA, 2026)
This study aims to systematically review the literature on strategies for improving Small and Medium-sized Enterprises (SMEs) performance through sustainability practices by emphasizing the roles of co-innovation and entrepreneurial orientation. A qualitative approach using the Systematic Literature Review (SLR) method was employed following the PRISMA 2020 guidelines. Relevant articles published between 2020 and 2024 were identified from reputable international databases. The findings reveal that sustainability practices positively influence SMEs performance by fostering technological innovation, enhancing collaborative knowledge sharing through co-innovation, and strengthening entrepreneurial orientation. Co-innovation facilitates access to external resources and knowledge, while entrepreneurial orientation enhances innovation capability and business adaptability. The review concludes that integrating sustainability practices, co-innovation, entrepreneurial orientation, and digital transformation constitutes an effective strategic framework for achieving sustainable competitive advantage and improving SMEs performance in an increasingly dynamic business environment